Optimalisasi Pembelajaran Bahasa Inggris Melalui Program English Camp dan Integrasi Inovasi Ide Bisnis Kewirausahaan - Siradjuddin , Suharti (Yayasan Habiburrahman Jamalu Bina Ummat, 2025)
This Community Service is intended for students in the form of an English Camp. This activity aims to improve the English skills of students in the Accounting study program at Makassar State University. This activity lasts for 3 days and 2 nights, starting from November 22 to 24, 2024, in Malino. The implementation of this activity includes opening, games, exercises, and English Presentations, where all participants must use English during this English Camp activities, both in and out of activities. The implementation of this activity also focuses on English presentation, where participants have prepared business idea innovations in advance and worked in groups before the English Camp was held. The results of their group discussions will be presented through PowerPoint media or the Canva model system, using English. The results of the implementation of this English Camp activity show a positive influence, one of which is the high motivation in speaking English, self-confidence, perseverance, and hard work in the implementation of this English Camp. Through this activity, it also shows that students are able to use English (although there are still many shortcomings) when situations and conditions require them to use it